EFFECT OF METFORMIN HYDROCHLORIDE IN CORRECTING HYPERINSULINEMIA AND HIGH LEPTIN LEVELS IN TREATMENT OF INFERTILE POLYCYSTIC PATIENTS - Irfan, Asma; Mughal, Irfan Afzal; Jalali, Samina (Journal of Ayub Medical College Abbottabad, 2013)
Background: Research conducted over PCOS by various groups in the world indicated the effect of Metformin on PCOS. Previous studies suggest that Glucophage by reducing hyper-insulinemia is clinically useful in the treatment of polycystic ovary syndrome (PCOS). Our Objective was to observe the role of Glucophage in treating infertility of polycystic patients within three months in Group A and six months in Group B patients. Another aim was to assess the decrease in hyper-insulinemia and Leptin levels by Glucophage in our population. Methods: This study was carried out at the Department of Obstetrics and Gynaecology, Pakistan Institute of Medical Sciences, and Noor Specialised Clinic Islamabad, from Oct 2004 to Apr 2008. One hundred and seventy women in Group A and 145 in Group B fulfilling the clinical and biochemical criteria for PCOS were enrolled. Glucophage was started at an oral dose of 500 mg/day and maintained at 1500 mg for 3 months or 6 months in both Groups. Besides ultrasonography, serum FSH, LH, fasting insulin, fasting blood sugar, glucose insulin ratio, Quantitative Insulin Sensitivity Check Index (QUICKI) and leptin levels were performed. After three months in Group A and six months in Group B these criteria were again assessed. Results: After 3 and 6 months of Metformin therapy, significant reduction in biochemical parameters was observed such as fasting glucose, insulin and leptin. Data were analysed using SPSS by paired t-test and ANOVA. Conclusion: Six months treatment with Glucophage proved to be better option for infertile PCOS. Keywords: Glucophage, PCOS, Hyperinsulinemia, Leptin